1997
DOI: 10.1002/jmri.1880070413
|View full text |Cite
|
Sign up to set email alerts
|

Experimental hepatic dysfunction: Evaluation by MRI with Gd‐EOB‐DTPA

Abstract: To investigate the potential of gadolinium (Gd)-ethoxybenzyl (EOB)-diethylenetriamine-pentaacetic acid (DTPA) for evaluating liver function, chemically induced hepatitis animal models were studied. The rats in group 1 underwent intraperitoneal administration of 2.0 ml/kg and those in group 2 underwent intraperitoneal administration of .5 ml/kg of 50% (V/V) carbon tetrachloride (CCl4) solution. The rats in group 3 served as controls. For rats of each group, the signal intensity of the liver was measured on T1-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
75
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 15 publications
3
75
0
1
Order By: Relevance
“…The mean MELD score in the patients with imaging stigmata of cirrhosis was 11.0 (SD 4.0; range [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], and the mean MELD score in patients without imaging stigmata of cirrhosis was 7.3 (SD 1.3; range 5-10) (P < 0.004). Because all patients in the subgroup without imaging stigmata of cirrhosis had MELD scores 10, this subgroup was compared with a subgroup that had imaging stigmata of cirrhosis and also had MELD scores 10 (n ¼ 45).…”
Section: Mri Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean MELD score in the patients with imaging stigmata of cirrhosis was 11.0 (SD 4.0; range [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], and the mean MELD score in patients without imaging stigmata of cirrhosis was 7.3 (SD 1.3; range 5-10) (P < 0.004). Because all patients in the subgroup without imaging stigmata of cirrhosis had MELD scores 10, this subgroup was compared with a subgroup that had imaging stigmata of cirrhosis and also had MELD scores 10 (n ¼ 45).…”
Section: Mri Resultsmentioning
confidence: 99%
“…Therefore, in patients with chronic parenchymal liver disease, the enhancement of the liver on the delayed images may be lower than expected in the patients with normal liver function (5)(6)(7). Several studies demonstrated that the rate and extent of excretion of Gd-EOB-DTPA into the biliary tree is reduced in patients with reduced hepatocyte function (6,7). When reviewing the hepatobiliary phase images of a patient with cirrhosis, one can be faced with a challenging question of whether the parenchymal enhancement is decreased, and, therefore, the approach to the hepatic lesion detection and characterization may need to be altered.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The relative enhancement correlated directly with the retransplantation-free survival rate [46]. Based on experiments in rats [47,48], Tajama et al were one of the first to be able to show the connection between reduced Gd-EOB enhancement and limited liver function in humans. Different lab values, the Child-Pugh score and the ICG test were correlated with the SNR of the liver for this purpose [49].…”
Section: Mri As Imaging-based Liver Function Testmentioning
confidence: 99%
“…Dynamic hepatocyte-specific contrast-enhanced MRI (DHCE-MRI) has previously been used in animal models for the evaluation of hepatic function in various experimental settings, either using semi-quantitative parameters or using deconvolutional analysis (DA) [22][23][24][25]. In human studies, liver parenchymal enhancement after administration of Gd-EOB-DTPA has been shown to correlate with ICG clearance and with liver cirrhosis as assessed by the CPS [26,27], and subsequent biliary excretion has been shown to be delayed in patients with impaired liver function [28].…”
mentioning
confidence: 99%